Symmetric molecules with 1,4-triazole moieties as potent inhibitors of tumour-associated lactate dehydrogenase-A - Altamimi, Abdul Malek S.; Alafeefy, Ahmed Mahmoud; Balode, Agnese; Vozny, Igor V.; Pustenko, Aleksandrs; El Shikh, Mohey Eldin M.; Alasmary, Fatmah Ali S.; Abdel-Gawad, Sherif A.; Žalubovskis, Raivis (Taylor & Francis, 2018)
A series of symmetric molecules incorporating aryl or pyridyl moieties as central core and 1,4-substituted triazoles as a side bridge was synthesised. The new compounds were investigated as lactate dehydro-genase (LDH, EC 1.1.1.27) inhibitors. The cancer associated LDHA isoform was inhibited with IC50 = 117–174 µM. Seven compounds exhibited better LDHA inhibition (IC50 117–136 µM) compared to known LDH inhibitor–galloflavin (IC50 157 µM). © 2017 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.